The Effects of Expressive Writing on Lung Function, Quality of Life, Medication Use, and Symptoms in Adults With Asthma. Issue 4 (May 2015) - Smith, Helen E.; Jones, Christina J.; Hankins, Matthew; Field, Andy; Theadom, Alice; Bowskill, Richard; Horne, Rob; Frew, Anthony J.
ABSTRACT Objectives Asthma is a chronic condition affecting 300 million people worldwide. Management involves adherence to pharmacological treatments such as corticosteroids and β-agonists, but residual symptoms persist. As asthma symptoms are exacerbated by stress, one possible adjunct to pharmacological treatment is expressive writing (EW). EW involves the disclosure of traumatic experiences which is thought to facilitate cognitive and emotional processing, helping to reduce physiological stress associated with inhibiting emotions. A previous trial reported short-term improvements in lung function. This study aimed to assess whether EW can improve lung function, quality of life, symptoms, and medication use in patients with asthma. Methods Adults (18–45 years) diagnosed as having asthma requiring regular inhaled corticosteroids were recruited from 28 general practices in South East England (n = 146). In this double-blind randomized controlled trial, participants were allocated either EW or nonemotional writing instructions and asked to write for 20 minutes for 3 consecutive days. Lung function (forced expired volume in 1 second [FEV1]% predicted), quality of life (Mark's Asthma Quality of Life Questionnaire), asthma symptoms (Wasserfallen Symptom Score Questionnaire), and medication use (inhaled corticosteroids and β-agonist) were recorded at baseline, 1, 3, 6, and 12 months. Results Hierarchical linear modeling indicated no significant main effects between time and condition on any outcomes. Post hoc analyses revealed that EW improved lung function by 14% for 12 months for participants with less than 80% FEV1% predicted at baseline (β = 0.93, p = .002) whereas no improvement was observed in the control condition (β = 0.10, p = .667). Conclusions EW seems to be beneficial for patients with moderate asthma (<80% FEV1% predicted). Future studies of EW require stratification of patients by asthma severity. Trial Registration: ISRCTN82986307